Code-Switching in the Classroom of Doti - Neupane, Padam Prasad (DMC Research Journal, 2018)
This article entitled 'code-switching in the classroom of Doti' is an attempt to identify the types of code-switching and reasons behind those code-switching which take place in the Nepali or Doteli language in English medium classes. The data of the study were collected through both primary and secondary sources. The sample population consists of 10 teachers teaching in secondary level English teachers of Silgadhi, Doti.The researcher used questionnaire as a tool for data collection. The study shows that teachers switch Nepali and Doteli code in English medium classes. Code- switching in the English medium classes occur in all the levels of language. Teachers' lack of competency in the target language and existence of multiplicity of language and cultures are the main reasons of code-switching. Sometimes, they switch Doteli code to break monotony and create fun in English medium classes.